Melt emulsion extrusion process for preparing thermoplastic polymer particles
The preparation of highly spherical thermoplastic polymer particles by melt emulsion extrusion method solves the problem of insufficient powder flowability and filling efficiency in the prior art, achieves better flowability and filling efficiency, and reduces the gaps in 3D printed items.
Patent Information
- Application Number
- CN202010883537.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-30
- Filing Date
- 2020-08-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-08-28
AI Technical Summary
The existing thermoplastic polymer powder particles have poor powder flow performance and filling efficiency during the 3D printing process, resulting in weak structures and void formation.
Highly spherical thermoplastic polymer particles were prepared by using a molten emulsion extrusion method, and the thermoplastic polymer was mixed with the carrier by applying a high shear rate in the extruder, cooling to form solidified particles and separating them from the carrier.
The prepared thermoplastic polymer particles have good flowability and filling efficiency, reducing void formation in 3D printed items and improving the mechanical integrity of the structure.
Smart Images

Figure CN112454723B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to thermoplastic polymer particles and methods of making such particles. Such particles, especially highly spherical thermoplastic polymer particles, can be used, among other things, as raw materials for additive manufacturing. Background Art
[0002] Three-dimensional (3D) printing (also known as additive manufacturing) is a rapidly growing field of technology. Although 3D printing has traditionally been used for rapid prototyping activities, the technology is increasingly being used to produce commercial and industrial objects that may have structural and mechanical tolerances that are very different from those of rapid prototypes.
[0003] 3D printing operates by depositing either (a) small droplets or streams of molten or solidifiable material or (b) powder particles in precise deposition locations for subsequent consolidation into larger items, which may have any number of complex shapes. Such deposition and consolidation processes are typically performed under computer control to provide layer-by-layer buildup of larger items. In a specific example, consolidation of powder particles may be performed in a 3D printing system using a laser to facilitate selective laser sintering (SLS). Incomplete interlayer fusion may create structural weak points, which may be problematic for printing items with tight structural and mechanical tolerances.
[0004] Powder particles that can be used for 3D printing include thermoplastic polymers (including thermoplastic elastomers), metals, and other solidifiable substances. Although a wide variety of thermoplastic polymers are known, relatively few thermoplastic polymers have properties suitable for 3D printing, especially when powder bed fusion (PBF) is used. Additive manufacturing methods using powder materials include PBF, selective laser sintering (SLS), selective heat sintering (SHM), selective laser melting (SLM), electron beam melting (EBM), binder jetting, and multi-jet melting (MJF). In the SLS printing method, energy from a high-power laser fuses the particles together. Typical thermoplastic polymers suitable for 3D printing include those with a clear melting point and a recrystallization point about 20°C to 50°C lower than the melting point. This difference allows more efficient coalescence between adjacent polymer layers, thereby promoting improved structural and mechanical integrity.
[0005] In order to achieve good printing performance using powder particles (especially polymer powder particles), the powder particles need to maintain good flow characteristics in the solid state. The flow characteristics can be evaluated, for example, by measuring the fraction of powder particles in the sample that can pass through a standard sieve of a specified size and / or measuring the angle of repose. A high fraction of sievable powder particles can indicate that the particles exist in the form of non-agglomerated, essentially separate particles, which can be a feature of a ready-to-use powder flow. In addition, a lower value of the angle of repose can be a feature of a ready-to-use powder flow. A relatively narrow particle size distribution in the sample and the regularity of the particle shape can also help promote good powder flow properties.
[0006] Commercial powder particles are typically obtained by cryogenic grinding or precipitation processes, which can produce irregular particle shapes and wide particle size distributions. Irregular particle shapes can lead to poor powder flow properties during 3D printing. In addition, powder particles with irregular shapes (especially those obtained from current commercial processes) can lead to poor filling efficiency after deposition and consolidation, thereby widely forming voids in the printed objects because the powder particles are not tightly packed together during deposition. Wide particle size distributions can similarly be problematic in this regard. Although poor powder flow properties can be addressed to a certain extent by dry mixing with fillers and flow aids, these techniques may have limited effectiveness for softer polymer materials (such as elastomers) due to particle aggregation. Summary of the invention
[0007] The present disclosure relates to thermoplastic polymer particles and melt emulsion extrusion methods for preparing such particles. Such particles, especially highly spherical thermoplastic polymer particles, can be used as raw materials for additive manufacturing, among other things.
[0008] Described herein is a method comprising: mixing a mixture comprising a thermoplastic polymer and a carrier fluid immiscible with the thermoplastic polymer in an extruder at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the carrier fluid; cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles, the solidified particles comprising thermoplastic polymer particles having a roundness of 0.90 or greater and comprising the thermoplastic polymer; and separating the solidified particles from the carrier fluid.
[0009] Described herein is a composition comprising: particles comprising thermoplastic polymer particles having a circularity of 0.90 or greater. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] The following drawings are included to illustrate certain aspects of the embodiments and should not be construed as exclusive embodiments. The disclosed subject matter is capable of considerable modification, alteration, combination, and equivalents in form and function, as will occur to those skilled in the art having the benefit of this disclosure.
[0011] Figure 1 is a flow chart of a non-limiting example method 100 of the present disclosure.
[0012] Figure 2 are non-limiting examples of extruder configurations.
[0013] Figure 3 is a scanning electron micrograph of polyamide particles.
[0014] Figure 4 is a scanning electron micrograph of polyamide particles.
[0015] Figure 5 is a scanning electron micrograph of polyamide particles.
[0016] Figure 6 is a scanning electron micrograph of polyamide particles.
[0017] Figure 7 is a scanning electron micrograph of polyamide particles.
[0018] Figure 8 is a scanning electron micrograph of polyamide particles.
[0019] Fig. 9 is a scanning electron micrograph of polyamide particles.
[0020] Fig.10 is a scanning electron micrograph of polyamide particles.
[0021] Fig.11 is a scanning electron micrograph of polyamide particles. DETAILED DESCRIPTION
[0022] The present disclosure relates to thermoplastic polymer particles and melt emulsion extrusion methods for preparing such particles. Such particles, especially highly spherical thermoplastic polymer particles, can be used as raw materials for additive manufacturing, among other things.
[0023] More specifically, the thermoplastic polymer particles described herein are prepared by an extrusion emulsification method, wherein the thermoplastic polymer is dispersed in a carrier fluid that is immiscible with the thermoplastic polymer in the form of a melt. Sufficient shear is applied in the extruder to form droplets in the carrier fluid from the thermoplastic polymer melt. Emulsion stabilizers (e.g., such as nanoparticles and / or surfactants) can be used to affect the surface tension at the interface between the carrier fluid and the thermoplastic polymer melt, and thus affect the properties of the resulting thermoplastic polymer particles. The dispersion of the thermoplastic polymer melt in the carrier fluid is cooled to solidify the thermoplastic polymer into particles. Advantageously, the emulsion extrusion process described herein can be operated continuously, which provides a potential scalable method for the industrial level production of highly spherical thermoplastic polymer particles with uniform size.
[0024] Without being limited by theory, during the melt emulsification process, the emulsion stabilizer is mainly located at the interface between the polymer melt and the carrier fluid. Therefore, when the mixture is cooled, the emulsion stabilizer remains at the interface. Advantageously, the emulsion stabilizer at the surface of the resulting particles can contribute to the flow characteristics of the resulting particles.
[0025] As previously described, conventional methods of forming thermoplastic polymer particles having good flowability include at least two steps, which include first forming (e.g., by cryogenic grinding or precipitation processes) and purifying the particles, and secondly coating the particles to some extent with a flow enhancer such as nanoparticle silica, carbon black, or PTFE particles. The methods described herein advantageously prepare thermoplastic polymer particles having a coating that enhances the flowability of the particles in one process.
[0026] In addition, without being limited by theory, the method of the present disclosure appears to produce particles with more uniform coverage of the emulsion stabilizer, which can further improve flowability. Enhanced flowability is particularly beneficial for additive manufacturing applications, such as 3D printing.
[0027] In a preferred embodiment, the present disclosure describes a method comprising:
[0028] providing a mixture comprising an emulsion stabilizer, a thermoplastic polymer, and a carrier fluid that is immiscible with the thermoplastic polymer at a temperature greater than the melting point or softening temperature of the thermoplastic polymer;
[0029] shearing the mixture in an extruder to form an emulsion at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the carrier fluid as droplets of molten thermoplastic polymer, wherein the emulsion stabilizer is between the thermoplastic polymer and the carrier fluid;
[0030] wherein the emulsion stabilizer comprises nanoparticles having a D50 of 1 nm to 500 nm, and the nanoparticles comprise the following particles: metal oxide nanoparticles, carbon black, or any combination thereof;
[0031] cooling the emulsion to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles in the presence of nanoparticles, the solidified particles having a roundness of 0.90 or greater and comprising the thermoplastic polymer and the nanoparticles forming a coating on an outer surface of the solidified particles;
[0032] wherein the emulsion is cooled in the extruder and / or after the emulsion leaves the extruder to form solidified particles; and
[0033] The solidified particles are separated from the carrier fluid.
[0034] In another preferred embodiment, the present disclosure describes a method comprising:
[0035] Adding an emulsion stabilizer comprising nanoparticles having a D50 of 1 nm to 500 nm, a thermoplastic polymer, and a carrier fluid to an extruder in any order to prepare a mixture;
[0036] wherein the carrier fluid is immiscible with the thermoplastic polymer at a temperature greater than the melting point or softening temperature of the thermoplastic polymer, and the emulsion stabilizer is not an internal additive to the thermoplastic polymer; and
[0037] The nanoparticles include the following particles: metal oxide nanoparticles, carbon black or any combination thereof,
[0038] shearing the mixture in an extruder at a temperature of about 1°C to about 50°C above the melting point or softening temperature of the thermoplastic polymer and at a sufficiently high shear rate to form an emulsion comprising droplets of molten thermoplastic polymer dispersed in a carrier fluid, wherein the emulsion stabilizer is at the interface between the droplets of molten thermoplastic polymer and the carrier fluid;
[0039] Cooling the emulsion to below the melting point or softening temperature of the thermoplastic polymer at a rate of about 10° C. / hour to about 100° C. / second to form solidified particles in the presence of nanoparticles, the solidified particles having a roundness of 0.90 or greater and comprising the thermoplastic polymer and the nanoparticles forming a coating on an outer surface of the solidified particles;
[0040] wherein the emulsion is cooled in the extruder and / or after the emulsion leaves the extruder to form solidified particles; and
[0041] The solidified particles are separated from the carrier fluid.
[0042] Definition and test methods
[0043] As used herein, the term "immiscible" refers to a mixture of components that, when combined, form two or more phases that have less than 5 weight % solubility in each other at ambient pressure and room temperature or the melting points of the components if they are solid at room temperature. For example, polyethylene oxide having a molecular weight of 10,000 g / mol is solid at room temperature and has a melting point of 65° C. Thus, if a material that is liquid at room temperature and the polyethylene oxide have less than 5 weight % solubility in each other at 65° C., the polyethylene oxide is immiscible with the material.
[0044] As used herein, the term "thermoplastic polymer" refers to a plastic polymer material that can reversibly soften and harden when heated and cooled. Thermoplastic polymers encompass thermoplastic elastomers.
[0045] As used herein, the term "elastomer" refers to a copolymer comprising a crystalline "hard" segment and an amorphous "soft" segment. For example, in the case of a polyurethane, the crystalline segment may include a portion of a polyurethane having carbamate functional groups and optional chain extender groups, and the soft segment may include a polyol.
[0046] As used herein, the term "polyurethane" refers to the polymer reaction product between a diisocyanate, a polyol, and an optional chain extender.
[0047] As used herein, the term "oxide" refers to both metal oxides and non-metal oxides. For the purposes of this disclosure, silicon is considered a metal.
[0048] As used herein, the terms "associated," "associated," and grammatical variations thereof between an emulsion stabilizer and a surface refer to chemical bonding and / or physical adhesion of the emulsion stabilizer to the surface. Without being limited by theory, it is believed that the association between the polymers described herein and the emulsion stabilizer is primarily physical adhesion via hydrogen bonding and / or other mechanisms. However, chemical bonding may occur to some extent.
[0049] As used herein, the term "embedded" with respect to nanoparticles and polymer particle surfaces means that the nanoparticles extend at least partially into the surface such that the polymer contacts the nanoparticles to a greater extent than would be achieved if the nanoparticles were simply laid on the polymer particle surface.
[0050] As used herein, D10, D50, D90 and diameter span are primarily used herein to describe particle size. As used herein, the term "D10" refers to the diameter at which 10% of the sample (on a volume basis unless otherwise specified) consists of particles with a diameter less than the stated diameter value. As used herein, the term "D50" refers to the diameter at which 50% of the sample (on a volume basis unless otherwise specified) consists of particles with a diameter less than the stated diameter value. As used herein, the term "D90" refers to the diameter at which 90% of the sample (on a volume basis unless otherwise specified) consists of particles with a diameter less than the stated diameter value.
[0051] As used herein, the terms "diameter span" and "span" and "span size" when referring to diameter provide an indication of the breadth of the particle size distribution and are calculated as (D90-D10) / D50 (again unless otherwise indicated, each D value is based on volume).
[0052] By using the Malvern MASTERSIZER TM Particle size was determined by light scattering techniques or analysis of optical digital micrographs of the ATmega 3000. Unless otherwise specified, light scattering techniques were used to analyze particle size.
[0053] For light scattering techniques, the control sample is the product of the trade name Quality Audit Standards QAS4002 TM Glass microspheres with diameters ranging from 15 μm to 150 μm were purchased from Malvern Analytical Ltd. Samples were analyzed as dry powders unless otherwise indicated. TM The particles to be analyzed were dispersed in air and analyzed using the 3000. The particle size was derived from a plot of bulk density versus size using the instrument software.
[0054] As used herein, when referring to sieving, the hole / sieve size is described in terms of United States Standard Sieve (ASTM E11-17).
[0055] As used herein, the terms "roundness" and "sphericity" with respect to particles refer to how close a particle is to a perfect sphere. To determine roundness, an optical microscopic image is taken of the particle. The perimeter (P) and area (A) of the particle in the plane of the microscopic image are calculated (e.g., using a SYSMEX FPIA 3000 particle shape and size analyzer, available from Malvern Instruments). The roundness of a particle is C EA / P, where C EAIt is the circumference of a circle whose area is equal to the area (A) of the actual particle.
[0056] As used herein, the term "sintering window" refers to the difference between the melting temperature (Tm) onset and the crystallization temperature (Tc) onset or (Tm-Tc) onset. Tm, Tm (onset), Tc, and Tc (onset) are determined by differential scanning calorimetry at a ramp rate of 10 ° C / min and a cooling rate of 10 ° C / min according to ASTM E794-06 (2018).
[0057] As used herein, the term "extruder" refers to a device having a barrel section having one or more screws or screw-like structures that convey material along the length of the barrel section. Extruders described herein do not necessarily include a die through which the material passes when the barrel section or other parts of the extruder leave. Extruders may be single screw extruders, twin screw extruders, or extruders comprising more than two screws, wherein the screws may be co-rotating or counter-rotating. Extruders are not limited by the amount of material that can be processed by the extruder. For example, extruders may be laboratory extruders (or one-time feed extruders) or larger continuous extruders.
[0058] As used herein, the term "shear" refers to stirring or similar processes that cause mechanical agitation in a fluid.
[0059] As used herein, the term "aspect ratio" refers to the length divided by the width, wherein the length is greater than the width.
[0060] Unless otherwise indicated, the melting point of the polymers was determined by ASTM E794-06 (2018) with a 10°C / min ramp rate and cooling rate.
[0061] Unless otherwise indicated, the softening temperature or softening point of a polymer is determined by ASTM D6090-17.The softening temperature can be measured using a cup and ball apparatus commercially available from Mettler-Toledo using a 0.50 gram sample at a heating rate of 1°C / min.
[0062] The angle of repose is a measure of the flowability of a powder. Angle of repose measurements were determined using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices" using a Hosokawa Micron Powder Characterization Tester PT-R.
[0063] Hausner ratio (Hausner ratio, H r ) is a measure of the flowability of the powder and is determined by Hr =ρ 振实 / ρ 堆积 Calculate, where ρ 堆积 is the bulk density according to ASTM D6393-14, and ρ 振实 It is the tap density according to ASTM D6393-14.
[0064] As used herein, the term "embedded" with respect to nanoparticles and polymer particle surfaces means that the nanoparticles extend at least partially into the surface such that the polymer contacts the nanoparticles to a greater extent than would be achieved if the nanoparticles were simply laid on the polymer particle surface.
[0065] As used herein, unless otherwise specified, the viscosity of the carrier fluid is the kinematic viscosity at 25° C., measured in accordance with ASTM D445-19. For commercially available carrier fluids (e.g., PDMS oil), the kinematic viscosity data cited herein are provided by the manufacturer, whether measured in accordance with the aforementioned ASTM or another standard measurement technique.
[0066] Thermoplastic polymer particles and preparation method
[0067] Figure 1 1 is a flow chart of a non-limiting exemplary method 100 of the present disclosure. A thermoplastic polymer 102, a carrier fluid 104, and an optional emulsion stabilizer 106 are combined in an extruder at 108 to produce a mixture 110. The components 102, 104, and 106 may be added in any order and include mixing and / or heating during the combination of the components 102, 104, and 106 at 108.
[0068] The mixture 110 then passes through an extruder at 112 where a sufficiently high shear is applied to the mixture 110 at a temperature greater than the melting point or softening temperature of the thermoplastic polymer 102 to form a molten emulsion 114. Since the temperature is above the melting point or softening temperature of the thermoplastic polymer 102, the thermoplastic polymer 102 becomes a polymer melt. The shear rate should be high enough to disperse the polymer melt in the carrier fluid 104 in the form of droplets (i.e., polymer emulsion 114). Without being limited by theory, it is believed that, all other factors being equal, increasing shear should reduce the size of the droplets of polymer melt in the carrier fluid 104. However, at some point there may be diminishing returns to increasing shear and reducing droplet size, and / or there may be damage to the contents of the droplets, thereby reducing the quality of the particles produced therefrom.
[0069] The molten emulsion 114 inside and / or outside the extruder is then cooled at 116 to solidify the polymer droplets into thermoplastic polymer particles (also referred to as solidified thermoplastic polymer particles). The cooled mixture 118 may then be processed at 120 to separate the thermoplastic polymer particles 122 from other components 124 (e.g., carrier fluid 104, excess emulsion stabilizer 106, etc.), and to wash or otherwise purify the thermoplastic polymer particles 122. The thermoplastic polymer particles 122 include the thermoplastic polymer 102 and at least a portion of the emulsion stabilizer 106 coating the outer surface of the thermoplastic polymer particles 122. The emulsion stabilizer 106 or a portion thereof may be deposited on the thermoplastic polymer particles 122 as a uniform coating. In some cases, which may depend on non-limiting factors such as temperature (including cooling rate), type of thermoplastic polymer 102, and type and size of emulsion stabilizer 106, nanoparticles of emulsion stabilizer 106 may be at least partially embedded within the outer surface of thermoplastic polymer particles 122 during association with the outer surface of the thermoplastic polymer particles 122. Even if embedding does not occur, at least the nanoparticles within the emulsion stabilizer 106 may remain robustly associated with the thermoplastic polymer particles 122 to facilitate further use thereof. In contrast, dry blending already formed thermoplastic polymer microparticles (e.g., formed by cryogenic grinding or precipitation processes) with a flow aid (such as silica nanoparticles) does not produce a robust, uniform coating of the flow aid on the thermoplastic polymer microparticles.
[0070] Advantageously, the carrier fluid and wash solvent of the systems and methods described herein (eg, method 101) can be recycled and reused. One skilled in the art will recognize any necessary cleaning of the spent carrier fluid and solvent required during the recycling process.
[0071] The thermoplastic polymer 102 and the carrier fluid 104 should be selected so that they are immiscible at various processing temperatures (e.g., from room temperature to the processing temperature). An additional factor that may be considered is the difference (e.g., difference or ratio) in viscosity between the molten thermoplastic polymer 102 and the carrier fluid 104 at the processing temperature. The viscosity difference may affect droplet breakup and particle size distribution. Without being limited by theory, it is believed that when the viscosities of the molten thermoplastic polymer 102 and the carrier fluid 104 are too similar, the roundness of the product as a whole may be reduced, with the particles being more oval and more elongated structures observed.
[0072] Examples of thermoplastic polymers 102 include, but are not limited to, polyamides, polyurethanes, polyethylenes, polypropylenes, polyacetals, polycarbonates, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylene ethers, polyarylene sulfide, polysulfones, polyetherketones, polyamide-imides, polyetherimides, polyetheresters, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amides), grafted or non-grafted thermoplastic polyolefins. , functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / (meth) acrylate alkyl esters, functionalized or non-functionalized (meth) acrylic polymers, functionalized or non-functionalized ethylene / vinyl monomer / (meth) acrylate alkyl ester terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / (meth) acrylate alkyl ester / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and the like, and any combination thereof. Copolymers comprising one or more of the foregoing substances may also be used in the methods and systems of the present disclosure.
[0073] The thermoplastic polymer 102 in the compositions and methods of the present disclosure can be elastomeric or non-elastomeric. Some of the foregoing examples of thermoplastic polymers 102 can be elastomeric or non-elastomeric, depending on the exact composition of the polymer. For example, polyethylene, which is a copolymer of ethylene and propylene, can be elastomeric and independent of the amount of propylene in the polymer.
[0074] Thermoplastic elastomers generally belong to one of six categories: styrenic block copolymers, thermoplastic polyolefin elastomers, thermoplastic vulcanizates (also called elastomer alloys), thermoplastic polyurethanes, thermoplastic copolyesters, and thermoplastic polyamides (generally block copolymers containing polyamides). Examples of thermoplastic elastomers can be found in the following literature: Handbook of Thermoplastic Elastomers, 2nd edition, edited by BMW Walker and CP Rader, Van Nostrand Reinhold, New York, 1988. Examples of thermoplastic elastomers include, but are not limited to, elastomeric polyamides, polyurethanes, copolymers containing polyether blocks and polyamide blocks (PEBA or polyether block amides), methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, polybutadiene, polyisoprene, styrenic block copolymers and polyacrylonitrile, silicones, and the like. The elastic styrenic block copolymer may include at least one block selected from the group consisting of isoprene, isobutylene, butene, ethylene / butylene, ethylene-propylene, and ethylene-ethylene / propylene. More specific examples of elastic styrenic block copolymers include, but are not limited to, poly(styrene-ethylene / butylene), poly(styrene-ethylene / butylene-styrene), poly(styrene-ethylene / propylene), poly(styrene-ethylene / propylene-styrene), poly(styrene-ethylene / propylene-styrene-ethylene-propylene), poly(styrene-butadiene-styrene), poly(styrene-butylene-butadiene-styrene), and the like, and any combination thereof.
[0075] Examples of polyamides include, but are not limited to, polycaprolactam (nylon 6, polyamide 6, or PA6), poly(hexamethylene succinamide) (nylon 4,6, polyamide 4,6, or PA4,6), polyhexamethylene adipamide (nylon 6,6, polyamide 6,6, or PA6,6), polypentamethylene adipamide (nylon 5,6, polyamide 5,6, or PA5,6), polyhexamethylene sebacamide (nylon 6,10, polyamide 6,10, or PA6,10), polyundecanamide (nylon 11, polyamide 11, or PA11), polydodecaneamide (nylon 12, polyamide 12, or PA12), and polyhexamethylene terephthalamide (nylon 6T, polyamide 6 T or PA6T), nylon 10,10 (polyamide 10,10 or PA10,10), nylon 10,12 (polyamide 10,12 or PA10,12), nylon 10,14 (polyamide 10,14 or PA10,14), nylon 10,18 (polyamide 10,18 or PA10,18), nylon 6,18 (polyamide 6,18 or PA6,18), nylon 6,12 (polyamide 6,12 or PA6,12), nylon 6,14 (polyamide 6,14 or PA6,14), nylon 12,12 (polyamide 12,12 or PA12,12), etc. and any combination thereof. Copolyamides can also be used. Examples of copolyamides include, but are not limited to, PA 11 / 10,10, PA 6 / 11, PA 6,6 / 6, PA 11 / 12, PA 10,10 / 10,12, PA 10,10 / 10,14, PA 11 / 10,36, PA 11 / 6,36, PA 10,10 / 10,36, PA 6T / 6,6, etc. and any combination thereof. A polyamide followed by a first number of commas and a second number of main chain carbons is a polyamide having a first number of main chain carbons between nitrogens for segments without pendant =O groups and a second number of main chain carbons between two nitrogens for segments with pendant =O groups. As a non-limiting example, nylon 6,10 is [NH-(CH2)6-NH-CO-(CH2)8-CO] n A polyamide followed by a quantitative backslash number is a copolymer of the polyamide indicated by the numbers before and after the backslash.
[0076] Examples of polyurethanes include, but are not limited to, polyether polyurethanes, polyester polyurethanes, mixed polyether and polyester polyurethanes, and the like, and any combination thereof. Examples of thermoplastic polyurethanes include, but are not limited to, poly[4,4′-methylenebis(phenyl isocyanate)-alternative-1,4-butanediol / di(propylene glycol) / polycaprolactone], 1190A (a polyether polyurethane elastomer available from BASF), 1190A10 (a polyether polyurethane elastomer available from BASF), etc. and any combination thereof.
[0077] Compatibilizers may optionally be used to improve the blending efficiency and effectiveness of the thermoplastic polyester with one or more thermoplastic polymers. Examples of polymer compatibilizers include, but are not limited to, PROPOLDER TM MPP2020 20 (polypropylene, available from Polygroup Inc.), PROPOLDER TM MPP2040 40 (polypropylene, available from Polygroup Inc.), NOVACOM TM HFS2100 (maleic anhydride functionalized high density polyethylene polymer, available from Polygroup Inc.), KEN-REACT TM CAPS TM L TM 12 / L (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM CAPOW TM L TM 12 / H (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM LICA TM 12 (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM CAPS TM KPR TM 12 / LV (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM CAPOW TM KPR TM 12 / H (organic metal coupling agent, available from Kenrich Petrochemicals), KEN-REACT TM Titanates and zirconates (organometallic coupling agents available from Kenrich Petrochemicals), VISTAMAXX TM (ethylene-propylene copolymer, available from ExxonMobil), SANTOPRENE TM (a thermoplastic vulcanizate of EPDM and polypropylene, available from ExxonMobil), VISTALONTM (EPDM rubber, available from ExxonMobil), EXACT TM (plastomer, available from ExxonMobil), EXXELOR TM (polymer resin, available from ExxonMobil), FUSABOND TM M603 (random ethylene copolymer, available from DOW), FUSABOND TM E226 (anhydride-modified polyethylene, available from Dow Chemical Company (DOW)), BYNEL TM 41E710 (co-extrudable adhesive resin, available from DOW), SURLYN TM 1650 (ionomer resin, available from DOW), FUSABOND TM P353 (a chemically modified polypropylene copolymer available from DOW), ELVALOY TM PTW (ethylene terpolymer, available from DOW), ELVALOY TM 3427AC (copolymer of ethylene and butyl acrylate, available from DOW Chemical Company (DOW)), LOTADER TM AX8840 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 3210 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 3410 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 3430 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 4700 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM AX8900 (ethylene-acrylate based terpolymer, available from Arkema), LOTADER TM 4720 (ethylene-acrylate based terpolymer, available from Arkema), BAXXODUR TM EC 301 (amine of epoxy resin, available from BASF), BAXXODUR TMEC 311 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 303 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 280 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 201 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 130 (amine of epoxy resin, available from BASF), BAXXODUR TM EC 110 (amine of epoxy resin, available from BASF), styrene, polypropylene, polyamide, polycarbonate, EASTMAN TM G-3003 (a maleic anhydride grafted polypropylene available from Eastman), RETAIN TM (polymer modifier, available from DOW Chemical Company (DOW)), AMPLIFY TY TM (maleic anhydride grafted polymer, available from DOW Chemical Company (DOW)), INTUNE TM (olefin block copolymer, available from The Dow Chemical Company (DOW)), etc. and any combination thereof.
[0078] Thermoplastic polymer 102 may have a melting point or softening temperature of about 50°C to about 450°C (or about 50°C to about 125°C, or about 100°C to about 175°C, or about 150°C to about 280°C, or about 200°C to about 350°C, or about 300°C to about 450°C).
[0079] The thermoplastic polymer 102 may have a glass transition temperature (derived from ASTM E1356-08 (2014) using a 10°C / min ramp rate and cooling rate) of about -50°C to about 400°C (or about -50°C to about 0°C, or about -25°C to about 50°C, or about 0°C to about 150°C, or about 100°C to about 250°C, or about 150°C to about 300°C, or about 200°C to about 400°C).
[0080] The thermoplastic polymer 102 may optionally include an additive. Typically, the additive will be present before the thermoplastic polymer 102 is added to the mixture 110. Thus, the additive is dispersed throughout the thermoplastic polymer in the thermoplastic polymer melt droplets and the resulting thermoplastic polymer particles. Thus, for clarity, the additive is referred to herein as an "internal additive." The internal additive may be blended with the thermoplastic polymer just prior to preparing the mixture 110 or well in advance.
[0081] When describing the amounts of components in the compositions described herein (e.g., the mixture 110 and the thermoplastic polymer particles 122), internal additives are not accounted for based on the weight percentage of the thermoplastic polymer 102. For example, a composition comprising 1 wt% emulsion stabilizer is a composition comprising 0.9 g of emulsion stabilizer, 90 g of thermoplastic polymer, and 10 g of internal additive, based on the weight of 100 g of thermoplastic polymer 102 comprising 10 wt% of internal additive and 90 wt% of thermoplastic polymer.
[0082] The internal additive may be present in the thermoplastic polymer 102 at about 0.1 wt % to about 60 wt % (or about 0.1 wt % to about 5 wt %, or about 1 wt % to about 10 wt %, or about 5 wt % to about 20 wt %, or about 10 wt % to about 30 wt %, or about 25 wt % to about 50 wt %, or about 40 wt % to about 60 wt %) of the thermoplastic polymer 102. For example, the thermoplastic polymer 102 may include about 70 wt % to about 85 wt % of the thermoplastic polymer and about 15 wt % to about 30 wt % of the internal additive, such as glass fiber or carbon fiber.
[0083] Examples of internal additives include, but are not limited to, fillers, reinforcing agents, pigments, pH adjusters, and the like, and combinations thereof. Examples of fillers include, but are not limited to, glass fibers, glass particles, mineral fibers, carbon fibers, oxide particles (e.g., titanium dioxide and zirconium dioxide), metal particles (e.g., aluminum powder), and the like, and any combination thereof. Examples of pigments include, but are not limited to, organic pigments, inorganic pigments, carbon black, and the like, and any combination thereof.
[0084] Thermoplastic polymer 102 may be present in mixture 110 at about 5 wt % to about 60 wt % (or about 5 wt % to about 25 wt %, or about 10 wt % to about 30 wt %, or about 20 wt % to about 45 wt %, or about 25 wt % to about 50 wt %, or about 40 wt % to about 60 wt %) of the combined thermoplastic polymer 102 and carrier fluid 104.
[0085] Suitable carrier fluids 104 have a viscosity of about 1,000 cSt to about 150,000 cSt (or about 1,000 cSt to about 60,000 cSt, or about 40,000 cSt to about 100,000 cSt, or about 75,000 cSt to about 150,000 cSt) at 25°C.
[0086] Examples of the carrier fluid 104 include, but are not limited to, silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, polyethylene glycol with an alkyl terminal (e.g., a C1-C4 terminal alkyl group such as tetraethylene glycol dimethyl ether (TDG)), paraffin, liquid petrolatum, vison oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, corn germ oil, esters of lanolic acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and the like, and any combination thereof. Examples of silicone oils include, but are not limited to, polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane, and the like, and any combination thereof. The carrier fluid 104 may have one or more phases. For example, a polysiloxane modified with a fatty acid and a polysiloxane modified with a fatty alcohol (preferably the fatty acid and the fatty alcohol have similar chain lengths) may form a single-phase carrier fluid 104. In another example, a carrier fluid 104 comprising a silicone oil and a polyethylene glycol terminated with an alkyl group may form a two-phase carrier fluid 104.
[0087] The carrier fluid 104 may be present in the mixture 110 at about 40 wt % to about 95 wt % (or about 75 wt % to about 95 wt %, or about 70 wt % to about 90 wt %, or about 55 wt % to about 80 wt %, or about 50 wt % to about 75 wt %, or about 40 wt % to about 60 wt %) of the combined thermoplastic polymer 102 and the carrier fluid 104.
[0088] In some cases, carrier fluid 104 may have a relative humidity of about 0.6 g / cm 3 To about 1.5g / cm 3 The thermoplastic polymer 102 has a density of about 0.7 g / cm 3 To about 1.7g / cm 3 wherein the thermoplastic polymer has a similar, lower or higher density than the density of the carrier fluid.
[0089] Emulsion stabilizers used in the methods and compositions of the present disclosure may include nanoparticles (eg, oxide nanoparticles, carbon black, polymer nanoparticles, and combinations thereof), surfactants, and the like, and any combination thereof.
[0090] Oxide nanoparticles can be metal oxide nanoparticles, non-metal oxide nanoparticles or their mixtures. Examples of oxide nanoparticles include, but are not limited to, silicon dioxide, titanium dioxide, zirconium oxide, aluminum oxide, iron oxide, copper oxide, tin oxide, boron oxide, cerium oxide, thallium oxide, tungsten oxide, etc. and any combination thereof. Mixed metal oxides and / or non-metal oxides such as aluminosilicates, borosilicates and aluminoborosilicates are also included in the term metal oxide. Oxide nanoparticles can be hydrophilic or hydrophobic, which may be natural to the particles or the result of surface treatment of the particles. For example, silicon dioxide nanoparticles with hydrophobic surface treatment (such as dimethylsilyl, trimethylsilyl, etc.) can be used in the methods and compositions of the present invention. In addition, silicon dioxide with functional surface treatment (such as methacrylate functionality) can be used in the methods and compositions of the present invention. Non-functionalized oxide nanoparticles may also be suitable for use.
[0091] Commercially available examples of silica nanoparticles include, but are not limited to, those available from Evonik Particles (e.g. R812S (with hydrophobic modified surface and 260±30m 2 / g BET surface area of about 7nm average diameter silica nanoparticles), RX50 (with hydrophobic modified surface and 35±10m 2 / g BET surface area of about 40nm average diameter silica nanoparticles), 380 (with hydrophilic modified surface and 380±30m 2 / g of BET surface area of silica nanoparticles)) and the like and any combination thereof.
[0092] Carbon black is another type of nanoparticle that can be present as an emulsion stabilizer in the compositions and methods disclosed herein. Various grades of carbon black are familiar to those of ordinary skill in the art, and any of these grades of carbon black can be used herein. Other nanoparticles that can absorb infrared radiation can similarly be used.
[0093] Polymer nanoparticles are another type of nanoparticles that can be present in the form of emulsion stabilizers in the present disclosure. Suitable polymer nanoparticles can include one or more polymers that are thermosetting and / or crosslinked so that they do not melt when processed by melt emulsification according to the present disclosure. High molecular weight thermoplastic polymers with high melting points or decomposition points can similarly include suitable polymer nanoparticle emulsion stabilizers.
[0094] The nanoparticles can have an average diameter (D50 based on volume) of about 1 nm to about 500 nm (or about 10 nm to about 150 nm, or about 25 nm to about 100 nm, or about 100 nm to about 250 nm, or about 250 nm to about 500 nm).
[0095] Nanoparticles can have a size of about 10 m 2 / g to about 500m 2 / g(or about 10m 2 / g to about 150m 2 / g, or about 25m 2 / g to about 100m 2 / g, or about 100m 2 / g to about 250m 2 / g, or about 250m 2 / g to about 500m 2 / g) of BET surface area.
[0096] The nanoparticles can be included in the mixture 110 at a concentration of about 0.01 wt % to about 10 wt % (or about 0.05 wt % to about 1 wt %, or about 0.1 wt % to about 3 wt %, or about 1 wt % to about 5 wt %, or about 5 wt % to about 10 wt %) based on the weight of the thermoplastic polymer 102.
[0097] The surfactant may be anionic, cationic, nonionic or zwitterionic. Examples of surfactants include, but are not limited to, sodium lauryl sulfate, sorbitan oleate, poly[dimethylsiloxane-co-[3-(2-(2-hydroxyethoxy)ethoxy)propylmethylsiloxane], sodium docusate (sodium 1,4-bis(2-ethylhexyloxy)-1,4-dioxobutane-2-sulfonate), and the like, and any combination thereof. Commercially available examples of surfactants include, but are not limited to, DB-45 (sodium dodecyl diphenyl ether disulfonate, available from Pilot Chemicals), 80 (Sorbitan maleate nonionic surfactant), Surfactants (available from Stepan Company), TERGITOL TM TMN-6 (a water-soluble, nonionic surfactant available from DOW), TRITON TM X-100 (octylphenol ethoxylate, available from Sigma Aldrich), CA-520 (polyoxyethylene (5) isooctylphenyl ether, available from Sigma Aldrich), S10 (polyethylene glycol octadecyl ether, available from Sigma Aldrich), etc. and any combination thereof.
[0098] The surfactant may be included in the mixture 110 at a concentration of about 0.01 wt % to about 10 wt % (or about 0.01 wt % to about 1 wt %, or about 0.5 wt % to about 2 wt %, or about 1 wt % to about 3 wt %, or about 2 wt % to about 5 wt %, or about 5 wt % to about 10 wt %) based on the weight of the polyamide 102. Alternatively, the mixture 110 may not include (or be absent) a surfactant.
[0099] The weight ratio of nanoparticles to surfactant may be from about 1:10 to about 10:1 (or from about 1:10 to about 1:1, or from about 1:5 to about 5:1, or from about 1:1 to about 10:1).
[0100] As described above, components 102, 104, and 106 may be added to the extruder in any order. In a first example, all components may be premixed and optionally heated and then added to the extruder where sufficient shear and temperature are used to produce melt droplets dispersed in a carrier fluid. Alternatively, each component may be added separately at different locations along the length of the extruder. In another example, the emulsion stabilizer 106 may first be dispersed in the carrier fluid 104, optionally by heating, and the dispersion and thermoplastic polymer 102 may be added separately at different locations along the length of the extruder.
[0101] Figure 2 202a-202d. Each of these regions 202a-202d is different from the adjacent region in at least one characteristic. The characteristics may include, but are not limited to, maximum temperature, minimum temperature, maximum shear rate, minimum shear rate, mass flow rate, etc. and any combination thereof. For example, the screw design may vary along the length of the screw to achieve a desired shear rate in the region.
[0102] In the illustrated example, components 102, 104, and 106 may be added to the extruder at inlet 204 near the beginning of the first zone 202a and / or at inlet 206 near the beginning of the second zone 202b. The first zone 202a and the second zone 202b are used to combine the components 102, 104, and 106 at 108. The third zone 202c shown is where the melt emulsification process 112 occurs. Therefore, in the third zone 202c, the mixture 110 is at a temperature greater than the melting point or softening temperature of the thermoplastic polymer 102 and is subjected to a sufficiently high shear rate to disperse the thermoplastic polymer melt in the carrier fluid 104. In this example, the fourth zone 202d cools the molten emulsion 114 to a temperature lower than that of the third zone 202c. The temperature in the fourth zone 202d may be at, above, or below the melting point or softening temperature of the thermoplastic polymer 102. The molten emulsion 114 or the cooled mixture 118 (depending on the extent of cooling in the fourth zone 202d) then exits the extruder via an outlet 208. Additional cooling may be performed external to the extruder, if desired.
[0103] In the illustrated example, the inlet 204 may be used to add the emulsion stabilizer 106 dispersed in the carrier fluid 104, and the inlet 206 may be used to add the thermoplastic polymer 102, or vice versa. Alternatively, the inlet 204 may be used to add the thermoplastic polymer 102 and the carrier fluid 104, and the inlet 206 may be used to add the emulsion stabilizer 106. In yet another non-limiting example, the inlet 204 may be used to add the carrier fluid 104, the emulsion stabilizer 106, and a first portion of the thermoplastic polymer 102, and the inlet 206 may be used to add the second portion of the thermoplastic polymer 102.
[0104] Figure 2 is a non-limiting example of an extruder configuration 200. Other extruder configurations may include any number of zones (1 to 100 or more (or 1 to 10, or 2 to 15, or 3 to 20, or 5 to 20, or 10 to 50, or 25 to 75, or 50 to 100 or more) zones). In addition, other configurations may include any number of inlets (1 to 10 or more (or 1 to 5, or 1 to 4, or 1 to 3) inlets). For example, for high thermoplastic polymer concentrations, the polymer may be added to the mixture in stages on two or more inlets.
[0105] Processing 112 and forming molten emulsion 114 are performed under suitable processing conditions, which may include, but are not limited to, temperature, shear rate, time, throughput, etc., and any combination thereof.
[0106] The temperature of processing 112 and forming molten emulsion 114 should be a temperature greater than the melting point or softening temperature of thermoplastic polymer 102 and less than the decomposition temperature of any component 102, 104, and 106 in mixture 110. For example, the temperature of processing 112 and forming molten emulsion 114 can be about 1°C to about 50°C (or about 1°C to about 25°C, or about 5°C to about 30°C, or about 20°C to about 50°C) greater than the melting point or softening temperature of thermoplastic polymer 102, provided that the temperature of processing 112 and forming molten emulsion 114 is less than the decomposition temperature of any component 102, 104, and 106 in mixture 110.
[0107] The shear rate of processing 112 and forming molten emulsion 114 should be high enough to disperse the polymer melt in the form of droplets in carrier fluid 104. The droplets should include droplets having a diameter of about 1000 μm or less (or about 1 μm to about 1000 μm, or about 1 μm to about 50 μm, or about 10 μm to about 100 μm, or about 10 μm to about 250 μm, or about 50 μm to about 500 μm, or about 250 μm to about 750 μm, or about 500 μm to about 1000 μm).
[0108] The residence time of the mixture in the zone at the processing 112 temperature and shear rate used to form the molten emulsion 114 can be 10 seconds to 1 hour or longer (or 10 seconds to 5 minutes, or 30 seconds to 3 minutes, or 1 minute to 15 minutes, or 10 minutes to 45 minutes, or 30 hours to 1 hour).
[0109] The molten emulsion 114 may then be cooled at 116, either inside and / or outside the extruder. Cooling 116 may range from slow (e.g., allowing the molten emulsion to cool under ambient conditions) to fast (e.g., quenching). For example, the cooling rate may range from about 10°C / hour to about 100°C / second to almost instantaneous when quenching (e.g., in dry ice) (or about 10°C / hour to about 60°C / hour, or about 0.5°C / minute to about 20°C / minute, or about 1°C / minute to about 5°C / minute, or about 10°C / minute to about 60°C / minute, or about 0.5°C / second to about 10°C / second, or about 10°C / second to about 100°C / second).
[0110] During cooling, little or no shear may be applied to the molten emulsion 114. In some cases, the shear applied during heating may also be applied during cooling.
[0111] The cooled mixture 118 resulting from cooling 116 the molten emulsion 114 comprises solidified thermoplastic polymer particles 122 (or simply thermoplastic polymer particles) and other components 124 (e.g., carrier fluid 104, excess emulsion stabilizer 106, etc.). The thermoplastic polymer particles may be dispersed in the carrier fluid or settled in the carrier fluid.
[0112] The cooled mixture 118 may then be processed at 120 to separate the thermoplastic polymer particles 122 (or simply thermoplastic polymer particles 122) from other components 124. Suitable processing includes, but is not limited to, washing, filtering, centrifuging, decanting, and the like, and any combination thereof.
[0113] The solvent used to wash the thermoplastic polymer particles 122 should generally be (a) miscible with the carrier fluid 104 and (b) non-reactive with (e.g., non-swelling and non-dissolving) the thermoplastic polymer 102. The choice of solvent will depend on, among other things, the composition of the carrier fluid and the composition of the thermoplastic polymer 102.
[0114] Examples of solvents include, but are not limited to, aromatic hydrocarbons (e.g., toluene and / or xylene), aliphatic hydrocarbons (e.g., heptane, n-hexane and / or n-octane), alicyclic hydrocarbons (e.g., cyclohexane, cyclooctane), halogenated hydrocarbons (e.g., trichloroethane), alcohols (e.g., isopropanol), ketones (e.g., methyl ethyl ketone); esters (e.g., ethyl acetate), etc. and any combination thereof.
[0115] The solvent may be removed from the thermoplastic polymer particles 122 by drying using an appropriate method such as air drying, heat drying, reduced pressure drying, freeze drying, or a mixture thereof. Heating may preferably be performed at a temperature below the glass transition point of the thermoplastic polymer (e.g., about 50°C to about 150°C).
[0116] The thermoplastic polymer particles 122 separated from the other components 124 may optionally be further classified to prepare purified thermoplastic polymer particles 128. For example, in order to narrow the particle size distribution (or reduce the diameter span), the thermoplastic polymer particles 122 may be passed through a sieve having a pore size of about 10 μm to about 250 μm (or about 10 μm to about 100 μm, or about 50 μm to about 200 μm, or about 150 μm to about 250 μm).
[0117] In another exemplary purification technique, the thermoplastic polymer particles 122 may be washed with water to remove the surfactant while retaining substantially all of the nanoparticles associated with the surface of the thermoplastic polymer particles 122. In yet another exemplary purification technique, the thermoplastic polymer particles 122 may be blended with additives to achieve a desired final product. For clarity, such additives are referred to herein as "external additives" because they are blended with the thermoplastic particles 122 or other particles obtained by the methods described herein after the particles have solidified. Examples of external additives include glidants, other polymer particles, fillers, and the like, and any combination thereof.
[0118] In some cases, the surfactant used to prepare the thermoplastic polymer particles 122 may be undesirable in downstream applications. Thus, yet another exemplary purification technique may include at least substantially removing the surfactant from the thermoplastic polymer particles 122 (eg, by washing and / or pyrolysis).
[0119] Thermoplastic polymer particles 122 and / or purified thermoplastic polymer particles 128 (referred to as particles 122 / 128 ) can be characterized by composition, physical structure, and the like.
[0120] As described above, the emulsion stabilizer is at the interface between the polymer melt and the carrier fluid. Thus, when the mixture is cooled, the emulsion stabilizer remains at or near the interface. Thus, the structure of the particles 122 / 128 typically includes an emulsion stabilizer that is (a) dispersed on the outer surface of the particles 122 / 128 and / or (b) embedded in the exterior of the particles 122 / 128 (e.g., the exterior 1 volume %).
[0121] In addition, in the case where voids are formed inside the polymer melt droplets, the emulsion stabilizer 106 should generally be at the interface between the interior of the void and the thermoplastic polymer (and / or embedded in the interface). The void generally does not contain a thermoplastic polymer. Instead, the void may contain, for example, a carrier fluid, air, or be empty. The particles 122 / 128 may contain a carrier fluid at about 5% by weight or less (or about 0.001% by weight to about 5% by weight, or about 0.001% by weight to about 0.1% by weight, or about 0.01% by weight to about 0.5% by weight, or about 0.1% by weight to about 2% by weight, or about 1% by weight to about 5% by weight) of the particles 122 / 128.
[0122] Thermoplastic polymer 102 may be present in particle 122 / 128 at about 90% to about 99.5% by weight (or about 90% to about 95% by weight, or about 92% to about 97% by weight, or about 95% to about 99.5% by weight) of particle 122 / 128.
[0123] The emulsion stabilizer 106 may be present in the particles 122 / 128 at about 10% or less by weight (or about 0.01% to about 10% by weight, or about 0.01% to about 1% by weight, or about 0.5% to about 5% by weight, or about 3% to about 7% by weight, or about 5% to about 10% by weight) of the particles 122 / 128. When purified to at least substantially remove a surfactant or another emulsion stabilizer, the emulsion stabilizer 106 may be present in the particles 128 at less than 0.01% by weight (or 0% to about 0.01% by weight, or 0% to 0.001% by weight).
[0124] After forming thermoplastic microparticles according to the disclosure herein, at least a portion of nanoparticles (such as silica nanoparticles) can be disposed on the outer surface of the thermoplastic microparticles in the form of a coating. At least a portion of the surfactant (if used) can also be associated with the outer surface. The coating can be substantially uniformly disposed on the outer surface. As used herein with respect to the coating, the term "substantially uniform" refers to a uniform coating thickness in the surface position (particularly the entire outer surface) covered by the coating composition (e.g., nanoparticles and / or surfactant). The emulsion stabilizer 106 can form a coating covering at least 5% (or about 5% to about 100%, or about 5% to about 25%, or about 20% to about 50%, or about 40% to about 70%, or about 50% to about 80%, or about 60% to about 90%, or about 70% to about 100%) of the surface area of the particles 122 / 128. When purified to at least substantially remove a surfactant or another emulsion stabilizer, the emulsion stabilizer 106 may be present in the particles 128 at less than 25% (or 0% to about 25%, or about 0.1% to about 5%, or about 0.1% to about 1%, or about 1% to about 5%, or about 1% to about 10%, or about 5% to about 15%, or about 10% to about 25%) of the surface area of the particles 128. Image analysis of SEM micrographs may be used to determine the coverage of the emulsion stabilizer 106 on the exterior surfaces of the particles 122 / 128.
[0125] The particles 122 / 128 may have a D10 of about 0.1 μm to about 125 μm (or about 0.1 μm to about 5 μm, about 1 μm to about 10 μm, about 5 μm to about 30 μm, or about 1 μm to about 25 μm, or about 25 μm to about 75 μm, or about 50 μm to about 85 μm, or about 75 μm to about 125 μm), a D50 of about 0.5 μm to about 200 μm (or about 0.5 μm to about 10 μm, or about 5 μm to about 50 μm, or about 30 μm to about 100 μm, or about 30 μm to about 70 μm, or about 25 μm to about 50 μm, or about 50 μm to about 100 μm, or about 75 μm to about 150 μm, or about 100 μm to about 200 μm), and a D90 of about 3 μm to about 300 μm (or about 3 μm to about 15 μm, or about 10 μm to about 50 μm, or about 25 μm to about 75 μm, or about 70 μm to about 200 μm, or about 60 μm to about 150 μm, or about 150 μm to about 300 μm), where D10 < D50 < D90. The particles 122 / 128 may also have a diameter span of about 0.2 to about 10 (or about 0.2 to about 0.5, or about 0.4 to about 0.8, or about 0.5 to about 1.0, or about 1 to about 3, or about 2 to about 5, or about 5 to about 10). Without limitation, a diameter span value of 1.0 or greater is considered wide, and a diameter span value of 0.75 or less is considered narrow. Without limitation, a diameter span value of 1.0 or greater is considered wide, and a diameter span value of 0.75 or less is considered narrow.
[0126] In a first non - limiting example, the particles 122 / 128 may have a D10 of about 0.1 μm to about 10 μm, a D50 of about 0.5 μm to about 25 μm, and a D90 of about 3 μm to about 50 μm, where D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 0.2 to about 2.
[0127] In a second non - limiting example, the particles 122 / 128 may have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, where D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 1.0 to about 2.5.
[0128] In a third non - limiting example, the particles 122 / 128 may have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, where D10 < D50 < D90. The particles 122 / 128 may have a diameter span of about 0.6 to about 1.5.
[0129] In a fourth non-limiting example, the particles 122 / 128 may have a D10 of from about 75 μm to about 125 μm, a D50 of from about 100 μm to about 200 μm, and a D90 of from about 125 μm to about 300 μm, where D10 < D50 < D90. The particles 122 / 128 may have a diameter span of from about 0.2 to about 1.2.
[0130] In a fifth non-limiting example, the particles 122 / 128 may have a D10 of from about 1 μm to about 50 μm (or from about 5 μm to about 30 μm, or from about 1 μm to about 25 μm, or from about 25 μm to about 50 μm), a D50 of from about 25 μm to about 100 μm (or from about 30 μm to about 100 μm, or from about 30 μm to about 70 μm, or from about 25 μm to about 50 μm, or from about 50 μm to about 100 μm), and a D90 of from about 60 μm to about 300 μm (or from about 70 μm to about 200 μm, or from about 60 μm to about 150 μm, or from about 150 μm to about 300 μm), where D10 < D50 < D90. The particles 122 / 128 may also have a diameter span of from about 0.4 to about 3 (or from about 0.6 to about 2, or from about 0.4 to about 1.5, or from about 1 to about 3).
[0131] The particles 122 / 128 may have a roundness of about 0.9 or greater (or from about 0.90 to about 1.0, or from about 0.93 to about 0.99, or from about 0.95 to about 0.99, or from about 0.97 to about 0.99, or from about 0.98 to 1.0).
[0132] The particles 122 / 128 may have an angle of repose of from about 20° to about 45° (or from about 25° to about 35°, or from about 30° to about 40°, or from about 35° to about 45°).
[0133] The particles 122 / 128 may have a Hausner ratio of from about 1.0 to about 1.5 (or from about 1.0 to about 1.2, or from about 1.1 to about 1.3, or from about 1.2 to about 1.35, or from about 1.3 to about 1.5).
[0134] The particles 122 / 128 may have a bulk density of from about 0.3 g / cm 3 to about 0.8 g / cm 3 (or from about 0.3 g / cm 3 to about 0.6 g / cm 3 , or from about 0.4 g / cm 3 to about 0.7 g / cm 3 , or from about 0.5 g / cm 3 to about 0.6 g / cm 3 , or from about 0.5 g / cm 3 to about 0.8 g / cm 3 ).
[0135] Depending on the temperature and shear rate of processing 112 and the composition and relative concentration of components 102, 104 and 106, different shapes of structures constituting particles 122 / 128 have been observed. Typically, particles 122 / 128 include substantially spherical particles (having a roundness of about 0.97 or greater). However, other structures have been observed in particles 122 / 128, including discs and elongated structures. Therefore, particles 122 / 128 may include one or more of the following: (a) substantially spherical particles with a roundness of 0.97 or greater, (b) disc structures with an aspect ratio of about 2 to about 10, and (c) elongated structures with an aspect ratio of 10 or greater. Each of the (a), (b) and (c) structures has an emulsion stabilizer dispersed on the outer surface of the (a), (b) and (c) structures and / or embedded in the exterior of the (a), (b) and (c) structures. At least some of the (a), (b) and (c) structures may be agglomerated. For example, (c) elongated structures may be laid on the surface of (a) substantially spherical particles.
[0136] The particles 122 / 128 may have a sintering window within 10°C, preferably within 5°C, of the sintering window of the thermoplastic polymer 102 (comprising one or more PP-polyamides and optionally one or more other thermoplastic polymers).
[0137] Applications of Thermoplastic Polymer Granules
[0138] The thermoplastic polymer particles described herein can be used in 3D printing processes, particularly those that use selective laser sintering to promote particle consolidation. The thermoplastic polymer particles of the present disclosure can exhibit properties superior to polymer particles having irregular shapes or wider particle distributions (such as those commercially available). In a non-limiting example, the thermoplastic polymer particles of the present disclosure can consolidate at lower laser powers and provide reduced void formation in articles prepared by 3D printing.
[0139] The 3D printing process of the present disclosure may include: depositing the thermoplastic polymer particles of the present disclosure onto a surface in a specified shape, and once deposited, heating at least a portion of the thermoplastic polymer particles to promote consolidation thereof and form a consolidated body (article), such that the consolidated body has a void percentage of about 1% or less after consolidation. For example, the heating and consolidation of the thermoplastic polymer particles may be performed in a 3D printing device using a laser, such that the heating and consolidation are performed by selective laser sintering.
[0140] Any thermoplastic polymer particles disclosed herein may be formulated in a composition suitable for 3D printing. The composition and type of the elastomeric microparticles may be selected based on various factors, such as, but not limited to, the laser power used for selective laser sintering, the type of article to be prepared, and the conditions of intended use of the article.
[0141] Examples of items that can be 3D printed using the thermoplastic polymer particles of the present disclosure include, but are not limited to, containers (e.g., for food, beverages, cosmetics, personal care compositions, pharmaceuticals, etc.), shoe soles, toys, furniture parts and decorative household items, plastic gears, screws, nuts, bolts, cable ties, automotive parts, medical supplies, prostheses, orthopedic implants, aviation / aircraft related parts, preparation of artifacts to aid learning in education, 3D anatomical models to assist surgery, robots, biomedical devices (orthotics), household appliances, dentistry, electronic devices, sporting goods, etc.
[0142] Other applications of the thermoplastic microparticles of the present disclosure may include, but are not limited to, use as fillers in paints and powder coatings, inkjet materials, and electrophotographic toners, etc. In some cases, the thermoplastic microparticles may have other preferred characteristics, such as diameter and span, that may be useful for such other applications.
[0143] Non-limiting example embodiments
[0144] A first non-limiting example of the present disclosure is a method comprising: mixing a mixture comprising a thermoplastic polymer (e.g., a thermoplastic elastomer) and a carrier fluid immiscible with the thermoplastic polymer in an extruder at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the carrier fluid; cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles, the solidified particles comprising thermoplastic polymer particles having a roundness of 0.90 or greater and comprising the thermoplastic polymer; and separating the solidified particles from the carrier fluid. The first non-limiting exemplary method may also include one or more of the following: Element 1: wherein the mixture further comprises nanoparticles, and wherein the solidified particles further comprise a thermoplastic polymer and the nanoparticles associated with the outer surface of the solidified particles; Element 2: Element 1 and wherein at least some of the nanoparticles are embedded in the outer surface of the solidified particles; Element 3: Element 1 and wherein at least some of the solidified particles have voids, the voids comprising nanoparticles at the void / thermoplastic polymer interface; Element 4: Element 3 and wherein the nanoparticles are embedded in the void / thermoplastic polymer interface; Element 5: Element 3 and wherein the voids comprise a carrier fluid; Element 6: Element 1 and wherein the nanoparticles form a coating that covers less than 5% of the surface of the solidified particles; Element 7: Element 1 and wherein the nanoparticles form a coating that covers less than 5% of the surface of the solidified particles; Element 8: wherein the nanoparticles form a coating that covers at least 5% of the surface of the solidified particles; Element 9: Element 1 and wherein the nanoparticles form a coating that covers at least 50% of the surface of the solidified particles; Element 10: Element 1 and wherein the solidified particles further include elongated structures on the surface of the solidified particles, wherein the elongated structures comprise a thermoplastic polymer and the nanoparticles are associated with the outer surfaces of the elongated structures; Element 11: Element 1 and wherein the nanoparticles are present in the mixture at 0.01 wt % to 10 wt % based on the weight of the thermoplastic polymer; Element 12: Element 1 and wherein the nanoparticles have an average diameter of 1 nm to 500 nm; Element 13: Element 1 and wherein the nanoparticles have an average diameter of 10 nm to 500 nm; 2 / g to 500m 2 / g of BET surface area; Element 14: wherein at least some of the thermoplastic polymer particles have voids containing a carrier fluid; Element 15: wherein the thermoplastic polymer is present in the mixture at 5% to 60% by weight of the mixture; Element 16: wherein the thermoplastic polymer is selected from the group consisting of: polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), Poly(hexylene terephthalate), polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylene ethers, polyarylene sulfide, polysulfones, polyetherketones, polyamide-imides, polyetherimides, polyetheresters, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amide), grafted or non-grafted thermoplastic polyolefins, functionalized or non-functionalized functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylate, functionalized or non-functionalized (meth)acrylic acid polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (S BM) block terpolymer, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resin, poly (ethylene / vinyl acetate), polybutadiene, polyisoprene, styrene block copolymer, polyacrylonitrile, silicone and any combination thereof; Element 17: wherein the melting point or softening temperature of the thermoplastic polymer is 50 ° C to 450 ° C; Element 18: wherein the carrier fluid is selected from: silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, polyethylene glycol with an alkyl terminal, paraffin, liquid vaseline, mink oil (vison oil), turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolic acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and any combination thereof;Element 19: Element 18 and wherein the silicone oil is selected from: polydimethylsiloxane, methylphenyl polysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenyl polysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenyl polysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenyl polysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenyl polysiloxane and any combination thereof; Element 20: wherein the carrier fluid has a viscosity of 1,000 cSt to 150,000 cSt at 25°C; Element 21: wherein the carrier fluid has a viscosity of 0.6 g / cm; 3 Up to 1.5g / cm 3 The density of thermoplastic polymers is 0.7 g / cm 3 Up to 1.7g / cm 3The density; Element 22: wherein the mixture further comprises a surfactant; Element 23: wherein the solidified particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, where D10 < D50 < D90; Element 24: wherein the solidified particles have a diameter span of about 0.2 to about 10; Element 25: wherein the solidified particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, where D10 < D50 < D90; Element 26: Element 25 and wherein the solidified particles have a diameter span of about 1.0 to about 2.5; Element 27: wherein the solidified particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, where D10 < D50 < D90; Element 28: Element 27 and wherein the solidified particles have a diameter span of about 0.6 to about 1.5; Element 29: wherein the solidified particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, where D10 < D50 < D90; Element 30: Element 29 and wherein the solidified particles have a diameter span of about 0.2 to about 1.2; Element 31: wherein the solidified particles have a roundness of about 0.97 to about 1.0; Element 32: wherein the solidified particles have a Hausner ratio of about 1.0 to about 1.5; Element 33: wherein the nanoparticles include oxide nanoparticles; Element 34: wherein the nanoparticles include carbon black; and Element 35: wherein the nanoparticles include polymer nanoparticles. Examples of combinations include, but are not limited to, combinations of Elements 1, 3, 4, and 5; combinations of Element 1 with two or more of Elements 2-13; combinations of Element 1 with one or more of Elements 14-35; combinations of Element 1 with one or more of Elements 2-13 and further combinations with one or more of Elements 14-35; combinations of two or more of Elements 14-35; and combinations of Elements 33-35.
[0145] A second non-limiting example of the present disclosure is a composition comprising: particles comprising thermoplastic polymer particles (e.g., thermoplastic elastomer particles) having a roundness of 0.90 or greater. The second non-limiting exemplary composition may also include one or more of the following: element 1; element 2; element 3; element 4; element 5; element 6; element 7; element 8; element 9; element 10; element 11; element 12; element 13; element 14; element 16; element 17; element 23; element 24; element 25; element 26; element 27; element 28; element 29; element 30; element 31; element 32; element 33; element 34; element 35; element 36: wherein the thermoplastic polymer is present at 90% to 99.5% by weight of the particle; and element 37: wherein the particle further comprises a surfactant associated with an outer surface of the particle. In addition, element 5 or 14 (alone or in combination below) can be further combined with one or more of elements 18, 19, 20 and 21. Examples of combinations include, but are not limited to: the combination provided in the first non-limiting example; the combination of elements 36 and 37; the combination of element 36 and / or element 37 with element 1 and optionally further combined with one or more of elements 2-13; the combination of element 36 and / or element 37 with one or more of elements 23-35 and optionally further combined with one or more of elements 1-13; and the combination of element 36 and / or element 37 with element 16 and / or element 17.
[0146] Terms
[0147] Item 1. A method comprising: mixing a mixture comprising a thermoplastic polymer (e.g., a thermoplastic elastomer) and a carrier fluid immiscible with the thermoplastic polymer in an extruder at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the carrier fluid; cooling the mixture to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles, the solidified particles comprising thermoplastic polymer particles having a roundness of 0.90 or greater and comprising the thermoplastic polymer; and separating the solidified particles from the carrier fluid.
[0148] Clause 2. The method of Clause 1, wherein the mixture further comprises an emulsion stabilizer (eg, nanoparticles and / or a surfactant), and wherein the solidified particles further comprise nanoparticles associated with an outer surface of the solidified particles.
[0149] Clause 3. The method of Clause 2, wherein the emulsion stabilizer comprises nanoparticles, and at least some of the nanoparticles are embedded in the outer surface of the solidified particles.
[0150] Clause 4. The method of Clause 2, wherein at least some of the solidified particles have voids containing nanoparticles at the void / thermoplastic polymer interface. Clause 5. The method of Clause 4, wherein the nanoparticles are embedded in the void / thermoplastic polymer interface.
[0151] Clause 6. The method of Clause 4, wherein the void contains a carrier fluid.
[0152] Clause 7. The method of Clause 2, wherein the emulsion stabilizer forms a coating that covers less than 5% of the surface of the solidified particles.
[0153] Clause 8. The method of Clause 2, wherein the emulsion stabilizer forms a coating that covers at least 5% of the surface of the solidified particles.
[0154] Clause 9. The method of Clause 2, wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the solidified particles.
[0155] Clause 10. The method of Clause 2, wherein the emulsion stabilizer forms a coating that covers at least 50% of the surface of the solidified particles.
[0156] Clause 11. The method of Clause 2, wherein the solidified particles further comprise elongated structures on a surface of the solidified particles, wherein the elongated structures comprise a thermoplastic polymer and the emulsion stabilizer is associated with an outer surface of the elongated structures.
[0157] Clause 12. The method of Clause 2, wherein the emulsion stabilizer is present in the mixture at 0.01 wt % to 10 wt % based on the weight of the thermoplastic polymer.
[0158] Item 13. The method of Item 2, wherein the nanoparticles have an average diameter of 1 nm to 500 nm.
[0159] Clause 14. The method according to clause 2, wherein the nanoparticles have a diameter of 10 m 2 / g to 500m 2 / g of BET surface area.
[0160] Clause 15. The method of Clause 2, wherein the nanoparticles comprise oxide nanoparticles.
[0161] Clause 16. The method of Clause 2, wherein the nanoparticles comprise carbon black.
[0162] Clause 17. The method of Clause 2, wherein the nanoparticles comprise polymer nanoparticles.
[0163] Clause 18. The method of Clause 1, wherein at least some of the thermoplastic polymer particles have voids that contain a carrier fluid.
[0164] Clause 19. The method of Clause 1, wherein the thermoplastic polymer is present in the mixture at 5% to 60% by weight of the mixture.
[0165] Clause 20. The method of claim 1, wherein the thermoplastic polymer is selected from the group consisting of:
[0166] Polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester (e.g., polylactic acid), polyether, polyether sulfone, polyether ether ketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyether ketone, polyamide-imide, polyetherimide, polyether ester, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amide), grafted or non-grafted thermoplastic polyolefins, functionalized or non-functionalized functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylate, functionalized or non-functionalized (meth)acrylic polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and any combination thereof.
[0167] Clause 21. The method of Clause 1, wherein the thermoplastic polymer has a melting point or softening temperature of 50°C to 450°C.
[0168] Item 22. The method according to Item 1, wherein the carrier fluid is selected from the group consisting of silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, alkyl-terminated polyethylene glycol, paraffin, liquid petrolatum, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, crabapple oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, cereal germ oil, esters of lanolin acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, Polysiloxane modified with fatty acid, polysiloxane modified with fatty alcohol, polysiloxane modified with polyoxyalkylene and any combination thereof Clause 23. The method according to Clause 22, wherein the silicone oil is selected from: polydimethylsiloxane, methylphenylpolysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenylpolysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenylpolysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenylpolysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenylpolysiloxane and any combination thereof.
[0169] Clause 24. The method of Clause 1, wherein the carrier fluid has a viscosity of 1,000 cSt to 150,000 cSt at 25°C.
[0170] Clause 25. The method according to clause 1, wherein the carrier fluid has a viscosity of 0.6 g / cm 3 Up to 1.5g / cm 3 The density of thermoplastic polymers is 0.7 g / cm 3 Up to 1.7g / cm 3 density.
[0171] Clause 26. The method of Clause 1, wherein the mixture further comprises an emulsion stabilizer (eg, nanoparticles and / or surfactants).
[0172] Clause 27. The method of Clause 1, wherein the solidified particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, wherein D10 <D50<D90。
[0173] Clause 28. The method of Clause 1, wherein the solidified particles have a diameter span of about 0.2 to about 10.
[0174] Clause 29. The method of Clause 1, wherein the solidified particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, wherein D10 <D50<D90。
[0175] Clause 30. The method of Clause 29, wherein the solidified particles have a diameter span of about 1.0 to about 2.5.
[0176] Clause 31. The method of Clause 1, wherein the solidified particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, wherein D10 <D50<D90。
[0177] Clause 32. The method of Clause 31, wherein the solidified particles have a diameter span of about 0.6 to about 1.5.
[0178] Clause 33. The method of Clause 1, wherein the solidified particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, wherein D10 <D50<D90。
[0179] Clause 34. The method of Clause 33, wherein the solidified particles have a diameter span of about 0.2 to about 1.2.
[0180] Clause 35. The method of Clause 1, wherein the solidified particles have a roundness of about 0.97 to about 1.0.
[0181] Clause 36. The method of Clause 1, wherein the solidified particles have a Hausner ratio of about 1.0 to about 1.5.
[0182] Clause 37. The method of Clause 1, wherein the thermoplastic polymer comprises a thermoplastic elastomer.
[0183] Clause 38. The method of Clause 1, wherein the thermoplastic polymer is a thermoplastic elastomer.
[0184] Clause 39. A composition comprising: particles comprising thermoplastic polymer particles (eg, thermoplastic elastomer particles) having a circularity of 0.90 or greater.
[0185] Clause 40. The composition of Clause 39, wherein the particles further comprise an emulsion stabilizer (eg, nanoparticles and / or surfactant) associated with the outer surface of the thermoplastic polymer particles.
[0186] Clause 41. The composition of Clause 40, wherein the emulsion stabilizer comprises nanoparticles and at least some of the nanoparticles are embedded in the outer surface of the particles.
[0187] Clause 42. The composition according to clause 40, wherein at least some of the particles have voids,
[0188] The voids contain nanoparticles at the void / thermoplastic polymer interface.
[0189] Item 43. The composition of Item 42, wherein the nanoparticles are embedded in the void / thermoplastic polymer interface.
[0190] Clause 44. The composition of clause 42, wherein the voids comprise a carrier fluid having a viscosity of 1,000 cSt to 150,000 cSt at 25°C. Clause 45. The composition of clause 40, wherein the particle further comprises an elongated structure comprising a thermoplastic polymer and the emulsion stabilizer is associated with an outer surface of the elongated structure.
[0191] Clause 46. The composition of Clause 40, wherein the emulsion stabilizer forms a coating that covers at least 5% of the surface of the particle.
[0192] Clause 47. The composition of Clause 40, wherein the emulsion stabilizer forms a coating that covers at least 25% of the surface of the particle.
[0193] Clause 48. The composition of Clause 40, wherein the emulsion stabilizer forms a coating that covers at least 50% of the surface of the particle.
[0194] Clause 49. The composition according to Clause 40, wherein the nanoparticles have an average diameter of 1 nm to 500 nm.
[0195] Clause 50. The composition according to clause 40, wherein the nanoparticles have a diameter of 10 m 2 / g to 500m 2 / g of BET surface area.
[0196] Clause 51. The composition of Clause 40, wherein the nanoparticles comprise oxide nanoparticles.
[0197] Clause 52. The composition of Clause 40, wherein the nanoparticles comprise carbon black.
[0198] Clause 53. The composition of Clause 40, wherein the nanoparticles comprise polymer nanoparticles.
[0199] Clause 54. The composition of Clause 39, wherein the thermoplastic polymer is present in an amount of 90% to 99.5% by weight of the particle.
[0200] Item 55. The composition according to Item 39, wherein the thermoplastic polymer is selected from the group consisting of: polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester (e.g., polylactic acid), polyether, polyethersulfone, polyetheretherketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymer, polyarylene ether, polyarylene sulfide, polysulfone, polyetherketone, polyamide-imide, polyetherimide, polyetherester, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amide), grafted or non-grafted Thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) type core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and any combination thereof.
[0201] Item 56. The composition of Item 39, wherein the thermoplastic polymer has a melting point or softening temperature of 50°C to 450°C.
[0202] Clause 57. The composition of clause 39, wherein the particles have a D10 of about 0.5 μm to about 125 μm, a D50 of about 1 μm to about 200 μm, and a D90 of about 70 μm to about 300 μm, wherein D10 <D50<D90。
[0203] Clause 58. The composition of Clause 57, wherein the particles have a diameter span of about 0.2 to about 10.
[0204] Clause 59. The composition of clause 39, wherein the particles have a D10 of about 5 μm to about 30 μm, a D50 of about 30 μm to about 70 μm, and a D90 of about 70 μm to about 120 μm, wherein D10 <D50<D90。
[0205] Clause 60. The composition of Clause 59, wherein the particles have a diameter span of about 1.0 to about 2.5.
[0206] Clause 61. The composition of clause 39, wherein the particles have a D10 of about 25 μm to about 60 μm, a D50 of about 60 μm to about 110 μm, and a D90 of about 110 μm to about 175 μm, wherein D10 <D50<D90。
[0207] Clause 62. The composition of Clause 61, wherein the particles have a diameter span of about 0.6 to about 1.5.
[0208] Clause 63. The composition of Clause 39, wherein the particles have a D10 of about 75 μm to about 125 μm, a D50 of about 100 μm to about 200 μm, and a D90 of about 125 μm to about 300 μm, wherein D10 <D50<D90。
[0209] Clause 64. The composition of Clause 63, wherein the solidified particles have a diameter span of about 0.2 to about 1.2.
[0210] Clause 65. The composition of Clause 39, wherein the particles have a roundness of about 0.97 to about 1.0.
[0211] Clause 66. The composition of Clause 39, wherein the particles have a Hausner ratio of about 1.0 to about 1.5.
[0212] Clause 67. The composition of Clause 39, wherein the thermoplastic polymer comprises a thermoplastic elastomer.
[0213] Clause 68. The composition of Clause 39, wherein the thermoplastic polymer is a thermoplastic elastomer.
[0214] Unless otherwise indicated, all numbers used in this specification and the related claims expressing the number of ingredients, characteristics (such as molecular weight), process conditions, etc. should be understood as being modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the following specification and the attached claims are approximate values, which may vary depending on the desired characteristics sought to be obtained by the embodiments of the present invention. At a minimum, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted in light of the number of significant digits reported and by applying customary rounding techniques.
[0215] One or more exemplary embodiments of the embodiments of the present invention disclosed herein are presented herein. For the sake of clarity, all features of physical implementation are not described or shown in this application. It should be understood that in the development of the physical implementation of the embodiments of the present invention, many specific decisions must be made to achieve the goal of the developer, such as meeting system-related constraints, business-related constraints, government-related constraints and other constraints, which vary and change over time due to implementation. Although the efforts made by the developer may be time-consuming, such efforts will be a routine task for those of ordinary skill in the art who benefit from the present disclosure.
[0216] Although compositions and methods are described herein as "comprising" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps.
[0217] In order to facilitate a better understanding of the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should in no way be construed as limiting or defining the scope of the present invention.
[0218] Example
[0219] Example 1. Preparation of polyamide 6 microparticles in a Haake small twin screw extruder with a high shear rotor. The carrier fluid was a PDMS oil having a viscosity of 30,000 cSt or 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are provided in Table 1. The order in which the components were added to the extruder was (a) the carrier fluid was added to the extruder, brought to temperature, and then room temperature polymer pellets were added to the heated carrier fluid in the extruder, or (b) the polymer pellets were added to the extruder, brought to temperature, and then the room temperature carrier fluid was added to the molten polymer in the extruder. The extruder was operated at 200 rpm for 30 minutes at temperature (see Table 1). The mixture was then discharged from the extruder onto a cold surface to provide rapid quench cooling. During heating and cooling at temperature, the torque of the extruder system was measured and no significant torque was detected.
[0220] Table 1
[0221]
[0222] Then through 90mm The resulting mixture was filtered through #1 filter paper (available from Sigma Aldrich) to separate the polyamide 6 particles from the carrier fluid. The particles were washed three times with 300 mL of ethyl acetate. The particles were then air dried overnight in an aluminum pan in a fume hood.
[0223] Then use the Malvern MASTERSIZER TM The size of the polyamide 6 particles was characterized using a 3000 and the morphology of the particles was characterized using SEM micrographs.
[0224] Table 2
[0225] sample D50(μm) Diameter span SEM micrograph 1-1 64 1.35 Figure 3 1-2 35 1.33 Figure 4 1-3 38 0.92 Figure 5 1-4 43 0.82 Figure 6 1-5 76 0.65 Figure 7 1-6 98 0.79 Figure 8 1-7 104 0.75 Fig. 9 1-8 96 0.83 Fig.10 1-9 100 0.60 Fig.11
[0226] This example shows the following general trends: (a) increasing oil viscosity decreases particle size and diameter span (e.g., compare 1-1 with 1-3 and 1-6 with 1-5), (b) increasing polymer loading increases particle size and decreases diameter span (e.g., compare 1-4 with 1-5 and 1-1 with 1-7), and (c) increasing processing temperature decreases particle size and diameter span (e.g., compare 1-8 with 1-5 and 1-1 with 1-2).
[0227] In addition, inductively coupled plasma was performed on particles that had been digested in a HNO3 / HF / H2O2 mixture using a closed container microwave or oven for digestion to determine the silica content associated with residual PDMS. The amount of silica present in the nine samples ranged from about 234 ppm to about 374 ppm. For the sample containing about 234 ppm silica, it was estimated that only about 0.62 g of PDMS was present per 1000 g of particles. Without being limited by theory, it is believed that the PDMS is primarily present on the surface of the particles.
[0228] Example 2. Preparation of polyamide 12 microparticles in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The carrier fluid was PDMS oil having a viscosity of 10,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are provided in Table 3. The polymer pellets were added to the extruder, brought to temperature, and then dispersed with The preheated carrier fluid of R812S silica nanoparticles was added to the molten polymer in the extruder. Other operating parameters are provided in Table 3. The mixture was then discharged into a container and allowed to cool to room temperature over several hours. Light scattering particle size data is also provided in Table 3.
[0229] Table 3
[0230]
[0231] * Relative to the total combined weight of PDMS oil and polyamide
[0232] **Compared to polyamide
[0233] Example 3. 1190A10 thermoplastic polyurethane (TPU) was added to a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25) and brought to temperature, and then dispersed with Preheated 10,000 cSt PDSM oil of RX50 silica nanoparticles was added to the molten polymer in the extruder. The conditions and results are presented in Table 4.
[0234] Table 4
[0235]
[0236]
[0237] * Relative to the total combined weight of PDMS oil and TPU
[0238] **Relative to TPU
[0239] Example 4. Preparation of polypropylene microparticles in a Haake small twin screw extruder with high shear rotors. The carrier fluid was a PDMS oil having a viscosity of 30,000 cSt or 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are provided in Table 15. The order in which the components were added to the extruder was (a) the carrier fluid was added to the extruder, brought to temperature, and then room temperature polymer pellets were added to the heated carrier fluid in the extruder, or (b) the polymer pellets were added to the extruder, brought to temperature, and then the room temperature carrier fluid was added to the molten polymer in the extruder. The polypropylene pellets were added at 30% solid loading (i.e., 18 g polypropylene in 60 g PDMS). The polypropylene used was PP D115A polypropylene homopolymer available from Baskem USA. The extruder was operated at about 200 rpm for 30 minutes at a temperature of 225° C. or 250° C. (see Table 5). The mixture was then discharged from the extruder onto a cold surface to provide rapid quench cooling. During heating and cooling at temperature, the torque of the extruder system was measured. The resulting mixture was then washed three times with 300 mL of heptane and passed through a 90 mm The resulting mixture was filtered through #1 filter paper (available from Sigma Aldrich) to separate the polypropylene particles from the carrier fluid. The particles were then allowed to air dry overnight in an aluminum pan in a fume hood. The morphology of the dried polypropylene particles was characterized using SEM micrographs and the Malvern MASTERSIZER TMThe size of the dried polypropylene particles was characterized using a 3000Aero S particle size analyzer. Thermal properties were evaluated using differential scanning calorimetry (DSC) to determine melting and crystallization temperatures. Inductively coupled plasma (ICP) determined the presence of residual silicone oil on the particles.
[0240] In this embodiment, the powder flow of the microparticles is characterized by sieving and angle of repose measurement. The sieving yield of the microparticles is determined in the following manner: a certain amount of microparticles is exposed to a 250 mm American Standard Sieve (ASTM E11) and the mass fraction of the microparticles passing through the sieve relative to the total amount of microparticles is determined. The sieve is manually used in the absence of the specific conditions of the force duration. ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices" is used to perform angle of repose measurement using Hosokawa Micron Powder Characterization Tester PT-R. The results are described in Table 5.
[0241] SEM micrographs depict smooth, round particles with a fairly wide size distribution. These particles were selectively laser sintered as a single layer in a Sharebot SnowWhite SLS printer. Particles made with 30,000 cSt oil required higher laser power to produce a robustly sintered single layer relative to particles made with 60,000 cSt oil. Particles made with 60,000 cSt oil exhibited extreme edge curling as laser power was increased.
[0242] Table 5
[0243]
[0244] Example 5. Polyamide 12 microparticles were prepared in a 25 mm twin screw extruder (Werner & Pfleiderer ZSK-25). The carrier fluid was PDMS oil having a viscosity of 60,000 cSt at room temperature. The concentrations of the components in the final mixture in the extruder are provided in Table 6. The polymer pellets were added to the extruder, brought to temperature, and then the preheated carrier fluid in which the silica nanoparticles were dispersed was added to the molten polymer in the extruder. Other operating parameters are provided in Table 6. The mixture was then discharged into a container and allowed to cool to room temperature over several hours. Light scattering particle size data is also provided in Table 6.
[0245] Table 6
[0246]
[0247] * Relative to the total combined weight of PDMS oil and polyamide
[0248] **Relative to the weight of polyamide
[0249] ***X24 is a silicon dioxide powder available from ShinEtsu, having an average particle size of 0.1 μm, a specific gravity of 1.8, and a water content of 2%.
[0250] Therefore, the present invention is well suited to achieve the goals and advantages mentioned and those inherent therein. The specific embodiments disclosed above are exemplary only, because the present invention can be modified and implemented in different but equivalent ways that are obvious to those skilled in the art who benefit from the teachings herein. In addition, it is expected that there is no limitation on the details of construction or design shown herein, except as described in the following claims. Therefore, it is obvious that the specific exemplary embodiments disclosed above can be changed, combined or modified, and all such changes are considered to be within the scope and essence of the present invention. The present invention disclosed exemplarily herein can be appropriately implemented in the absence of any element not specifically disclosed herein and / or any optional element disclosed herein. Although compositions and methods are described with "comprising", "containing" or "including" various components or steps, compositions and methods can also be "essentially composed of various components and steps" or "composed of various components and steps". All numbers and ranges disclosed above may change by some amount. Whenever a numerical range with a lower limit and an upper limit is disclosed, any number and any included range falling within the range are specifically disclosed. Specifically, each value range disclosed herein (in the form of "about a to about b", or equivalently, "about a to b", or equivalently, "about ab") should be understood to set forth each numerical value and range encompassed within the broader value range. In addition, the terms in the claims have their plain, ordinary meaning unless otherwise explicitly and clearly defined by the patentee. In addition, the indefinite articles "a" or "an" used in the claims are defined herein to mean that there is one or more than one of the element it introduces.
Claims
1. A method, comprising: providing a mixture comprising an emulsion stabilizer, a thermoplastic polymer, and a carrier fluid that is immiscible with the thermoplastic polymer at a temperature greater than the melting point or softening temperature of the thermoplastic polymer; shearing the mixture in an extruder to form an emulsion at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a shear rate high enough to disperse the thermoplastic polymer in the carrier fluid as droplets of molten thermoplastic polymer, wherein the emulsion stabilizer is between the thermoplastic polymer and the carrier fluid; wherein the emulsion stabilizer comprises nanoparticles having a D50 of 1 nm to 500 nm, and the nanoparticles comprise the following particles: metal oxide nanoparticles, carbon black, or any combination thereof; cooling the emulsion to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles in the presence of nanoparticles, the solidified particles having a roundness of 0.90 or greater and comprising the thermoplastic polymer and the nanoparticles forming a coating on an outer surface of the solidified particles; wherein the emulsion is cooled in the extruder and / or after the emulsion leaves the extruder to form solidified particles; and The solidified particles are separated from the carrier fluid. 2 . The method of claim 1 , wherein at least some of the nanoparticles are embedded in the outer surface of the solidified particles.
3. The method of claim 1 wherein at least some of the solidified particles have voids therein with the nanoparticles at a void / thermoplastic polymer interface.
4. The method of claim 3, wherein the nanoparticles are embedded in the void / thermoplastic polymer interface. The method of claim 3 , wherein the void contains the carrier fluid. The method of claim 1 , wherein the nanoparticles comprise silica nanoparticles.
7. The method of claim 1, wherein the solidified particles further comprise elongated structures on an outer surface of the solidified particles, wherein the elongated structures comprise the thermoplastic polymer.
8. The method of claim 1, wherein the emulsion stabilizer is present in the mixture at 0.01 wt% to 10 wt% based on the weight of the thermoplastic polymer.
9. The method of claim 1, wherein the thermoplastic polymer is present in the mixture at 5% to 60% by weight of the mixture.
10. The method according to claim 1, wherein the thermoplastic polymer is selected from the group consisting of polyamide, polyurethane, polyethylene, polypropylene, polyacetal, polycarbonate, polybutylene terephthalate PBT, polyethylene terephthalate PET, polyethylene naphthalate PEN, polytrimethylene terephthalate PTT, polyhexamethylene terephthalate, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyester, polylactic acid, polyether, polyether sulfone, polyether ether ketone, polyacrylate, polymethacrylate, polyimide, acrylonitrile butadiene styrene ABS, polyphenylene sulfide, vinyl polymer, polyarylether, polyarylene sulfide, polysulfone, polyether ketone, polyamide-imide, polyetherimide, polyether ester, copolymers comprising polyether blocks and polyamide blocks, grafted or non-grafted thermoplastic polyolefins, functionalized or non-functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / alkyl (meth)acrylates, functionalized or non-functionalized (meth)acrylic acid polymers, functionalized or non-functionalized ethylene / vinyl monomer / alkyl (meth)acrylate terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / alkyl (meth)acrylate / carbonyl terpolymers, methyl methacrylate-butadiene-styrene MBS core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) SBM block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride PVDF, phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and any combination thereof.
11. The method of claim 1, wherein the melting point or softening temperature of the thermoplastic polymer is from 50°C to 450°C.
12. The method of claim 1, wherein the temperature greater than the melting point or softening temperature of the thermoplastic polymer is 1°C to 50°C greater than the melting point or softening temperature of the thermoplastic polymer.
13. The method according to claim 1, wherein the carrier fluid is selected from the group consisting of silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, alkyl-terminated polyethylene glycol, paraffin, liquid petrolatum, mink oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, crabapple oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, corn germ oil, esters of lanolin acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and any combination thereof.
14. The method according to claim 1, wherein cooling is performed at a rate of 10°C / hour to 100°C / second.
15. The method of claim 1, wherein the extruder is selected from the group consisting of a single screw extruder, a twin screw extruder, and an extruder comprising more than two co-rotating or counter-rotating screws.
16. The method of claim 1 wherein the extruder has two or more zones at different temperatures.
17. The method of claim 1, wherein the solidified particles have a D10 of 0.5 μm to 125 μm, a D50 of 1 μm to 200 μm, and a D90 of 70 μm to 300 μm, wherein D10 <D50<D90。 18. The method of claim 1, wherein the solidified particles have a diameter span of 0.2 to 10.
19. A method comprising: Adding an emulsion stabilizer comprising nanoparticles having a D50 of 1 nm to 500 nm, a thermoplastic polymer, and a carrier fluid to an extruder in any order to prepare a mixture; wherein the carrier fluid is immiscible with the thermoplastic polymer at a temperature greater than the melting point or softening temperature of the thermoplastic polymer, and the emulsion stabilizer is not an internal additive to the thermoplastic polymer; and The nanoparticles include the following particles: metal oxide nanoparticles, carbon black or any combination thereof, shearing the mixture in an extruder at a temperature of 1°C to 50°C greater than the melting point or softening temperature of the thermoplastic polymer and at a sufficiently high shear rate to form an emulsion comprising droplets of molten thermoplastic polymer dispersed in a carrier fluid, wherein the emulsion stabilizer is at the interface between the droplets of molten thermoplastic polymer and the carrier fluid; cooling the emulsion to below the melting point or softening temperature of the thermoplastic polymer at a rate of 10° C. / hour to 100° C. / second to form solidified particles in the presence of nanoparticles, the solidified particles having a roundness of 0.90 or greater and comprising the thermoplastic polymer and the nanoparticles forming a coating on an outer surface of the solidified particles; wherein the emulsion is cooled in the extruder and / or after the emulsion leaves the extruder to form solidified particles; and The solidified particles are separated from the carrier fluid.
Citation Information
Patent Citations
Anti-bacterial metallo ionomer polymer nanocomposite filaments and methods of making the same
US20180007892A1
Method of producing fine particles of thermoplastic resin
US4863646A
Processes for preparing crosslinked resins and toner compositions therefrom
US5397671A